Hubungan Keterampilan Manajerial Kepala Sekolah, Iklim Sekolah, dan Moral Kerja Guru dengan Kinerja Guru SMA Negeri di Kota Merauke - Werang, Basilius Redan (Universitas Brawijaya, Indonesia, 2012)
This article reports a correlation study of principals’managerial skills, school climate, andteachers’work morale with teachers’performance. The study is aimed to know: (a) correlation betweenprincipals’managerial skills and school climate; (b) correlation between principals’managerial skillsand teachers’work morale; (c) correlation between principals’magerial skills and teachers’performance;(d) correlation between school climate and teachers’work morale; (e) correlation between school climateand teachers’performance; and (f) teachers’work morale and teachers’perfeormance. The study usedquantitative approach with descriptive-correlational design. The population included 90 teachers at StateSenior High Schools in Merauke city. Krecjie table was used to select the sample, that is, 71 teachers,82,56% of the population. The instrument was the form of questionnaires. This correlation study used pathmodel as the main data analysis. The results indicate that: (a) there is a positive and significant correlationbetween principals’managerial skills and school climate; (b) there is a positive and significant correlationbetween principals’managerial skills and teachers’work morale; (c) there is a positive and significantcorrelation between principals’managerial skills and teachers’performance; (d) there is a positive butnon-significant correlation between school climate and teachers’work morale; (e) there is a positive andsignificant correlation between school climate and teachers’performance; and (f) there is a positive andsignificant correlation between teachers’work morale and teachers’performance. Based on the results ofthe study, some suggestions should be taken into mind: (a) it is suggested that the government of Meraukeregency should take some strategic policies to facilitate principals, and the candidate of principals as well,to enhance their managerial skills; and (b) the principals should be recruited and selected from teacherswho are best in moral and personality.